THE TEACHING ANALYSIS OF READING COMPREHENSION: A CASE OF THE EIGHT GRADE STUDENTS OF SMP PGRI 01 SEMARANG - Yuli Anita; Dias Andris Susanto (ETERNAL (English Teaching Journal), 2013)
The objectives of the study are1) To know the teaching on reading comprehension at the eight grade of SMP PGRI 01 Semarang in academic year 2016/2017, 2) To know the problems faced by the teacher in teaching learning process of reading comprehension, and 3) To know the solutions of the problem faced in teaching learning process. This research uses qualitative method. The subject of this research was three teachers of class VIII A, VIII F, and VIII G. The instruments used in this research were observation sheet and interview, so the data use was collected through observation and interview. The result of the research showed that 1) the first teacher was first participant implementing reading stage in teaching and learning process. In first participant teaching, the researcher found the problem, it was the difficulty in implementing teaching reading. The solution first participant was make strategy to make student fun. 2) the second teacher was second participant. There was only one interaction, that was the teacher explained the materials then the students kept silent, or the students read something then the teachers listened to them. 3) the third teacher was third participant. The problem it was boredom, and the solution was making question and answer for them. Teachers concluded that reading comprehension is very effective but it can not to be the key in teaching and learning process. From the data which is obtained from documentation and observation inteaching English, the objectives of English teaching can be viewed from kinds of strategy and tecnique in teaching and learning process. Suggestion are 1) for teachers, it is better for them to use Team Games Tournament to teach the students in reading comprehension, 2) for students have to study harder and try to read English more and more, and 3) for the reader to be able to get more information and experiences in the purpose of developing and improving their knowledge, especially in reading comprehensio